Stigma, Trends, and Skincare Preferences among Male Consumers - Wifka Rahma Syauki; Avine, Diyah Ayu Amalia (Communicare : Journal of Communication Studies, 2024)
This study examines the stigma, inclinations, and skincare preferences of young consumers, with a particular focus on male, Millennials and Generation Z. Over recent years, the use of skincare products among women has witnessed a significant increase, driven by evolving perceptions and trends surrounding aging and wrinkles. Adopting a qualitative methodology, this research utilizes interviews to explore the factors motivating participants to use skincare products, their product choices, and their approaches to navigating social stigma associated with skincare use. Findings reveal that while stigma persists—particularly toward skincare products containing minerals—an increasing number of women view skincare as an essential element of self-care and personal improvement. Furthermore, technology and social media emerge as pivotal forces in shaping consumer preferences for specific products and services. The study also highlights emerging insights into male consumers’ responses to shifting social stigmas, offering valuable implications for marketing strategies and product innovation within the cosmetics industry.